Metal oxide nanoparticle dispersion

JP7639867B2Active Publication Date: 2025-03-05MURATA MFG CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023155617
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2023-09-21
Publication Date
2025-03-05
Estimated Expiration
2040-12-03

Smart Images

  • Figure 0007639867000003
    Figure 0007639867000003
  • Figure 0007639867000004
    Figure 0007639867000004
  • Figure 0007639867000005
    Figure 0007639867000005
Patent Text Reader

Abstract

To provide a metal double salt dispersion liquid with which a dispersion liquid of metal oxide nanoparticles having a small particle size and high dispersibility can be produced without requiring firing, and a method for producing the same.SOLUTION: A metal oxide nanoparticle dispersion liquid that includes metal oxide nanoparticles and a salt of a carboxylic acid and a strong base, wherein the carboxylic acid has a composition represented by R2COOH, in which R2 is a hydrogen atom or an alkyl group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal oxide nanoparticle dispersion. [Background technology]

[0002] Metal oxide fine particles are used in various fields, taking advantage of their properties such as low-temperature sinterability, large specific surface area, dispersibility in solvents, and quantum effect.

[0003] Methods for producing metal oxide fine particles include the build-down method, in which bulk metal oxide is pulverized, and the build-up method, in which particles are grown at the molecular level. Since there is a limit to how much fine particles can be produced by the build-down method, the build-up method is currently more commonly used.

[0004] Patent Document 1 discloses a method for producing metal oxide particles, in which an aqueous solution of a metal salt and an aqueous solution of a neutralizing agent are simultaneously added to an aqueous solution of a carboxylic acid compound to generate fine particles of metal hydroxide or hydrate, and then the resulting particles are calcined.

[0005] Non-Patent Document 1 discloses a method for producing a dispersion liquid in which zinc oxide nanoparticles are dispersed in ethanol, using lithium hydroxide as a base. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-139704 A [Non-patent literature]

[0007] [Non-Patent Document 1] EA Meulenkamp, ​​J.Phys.Chem. B,102,5566,(1998) Summary of the Invention [Problem to be solved by the invention]

[0008] However, the method described in Patent Document 1 requires calcining a metal hydroxide or metal hydrate, and therefore has the problem that the particle size of the resulting oxide particles is large and the dispersibility in the solvent is poor.

[0009] The method described in Patent Document 1 requires calcining the metal hydroxide or metal hydrate, and therefore there has been a demand for a method for obtaining oxide fine particles without calcining.

[0010] Furthermore, although the zinc oxide nanoparticles produced by the method described in Non-Patent Document 1 have high dispersibility immediately after production, there is a problem in that the dispersibility decreases over time.

[0011] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by using a dispersion of a double salt obtained by reacting a metal carboxylate with a base.

[0012] In other words, the present invention aims to provide a metal double salt dispersion that can produce a metal oxide nanoparticle dispersion having a small particle size and high dispersibility without the need for calcination, and a method for producing the same, as well as to provide a metal oxide nanoparticle dispersion that has excellent stability of dispersibility over time, and a method for producing the same. [Means for solving the problem]

[0013] The metal double salt dispersion of the present invention is a metal double salt dispersion containing an organic solvent and a metal double salt, and the metal double salt is M(R 1 COO) m-x-y (OH) x A y (H 2 O) z [where M is a metal element, R 1is a hydrogen atom or an alkyl group, A is an anion, m is the valence of the metal element M, 0 <x+y<m、x> 0, y≧0, z≧0.], and when the metal double salt dispersion is centrifuged at a relative centrifugal force of 10,000 G for 5 minutes, the proportion of metal elements that do not form precipitates among all metal elements contained in the entire metal double salt dispersion is 10.0 mol % or more.

[0014] The method for producing a metal double salt dispersion of the present invention includes a step of adding a strong base to a metal salt dispersion containing a metal carboxylate and an organic solvent, and is characterized in that, when the valence of a metal element constituting the metal carboxylate is m, the substance amount of the strong base relative to the substance amount of the metal carboxylate is 0.4 m or more and 0.9 m or less.

[0015] The metal oxide nanoparticle dispersion liquid of the present invention is characterized by containing metal oxide nanoparticles and an organic base having an amidine skeleton or a guanidine skeleton.

[0016] The method for producing a metal oxide nanoparticle dispersion of the present invention includes a preparation step of adding a strong base to a metal salt dispersion containing a metal carboxylate and an organic solvent to prepare a metal double salt dispersion, and a heating step of heating the metal double salt dispersion in the presence of water to obtain the metal oxide nanoparticle dispersion, wherein in the preparation step, when the valence of a metal element constituting the metal carboxylate is m, the substance amount of the strong base relative to the substance amount of the metal carboxylate is 0.4 m or more and 0.9 m or less, and the strong base includes an organic base having an amidine skeleton or a guanidine skeleton. Effect of the Invention

[0017] According to the present invention, it is possible to provide a metal double salt dispersion that can produce a metal oxide nanoparticle dispersion having a small particle size and high dispersibility without the need for calcination, and a method for producing the same. Furthermore, according to the present invention, it is possible to provide a metal oxide nanoparticle dispersion liquid in which the dispersibility of metal oxide nanoparticles is excellent in stability over time, and a method for producing the same. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a photograph of the metal double salt dispersions according to Example 1 and Comparative Example 1 after centrifugal separation. [Diagram 2] FIG. 2 is a photograph of the metal oxide nanoparticle dispersions according to Example 1 and Comparative Example 1 after centrifugal separation. [Diagram 3] FIG. 3 is a TEM image of the metal double salt according to Example 15. [Figure 4] FIG. 4 is a TEM image of the metal double salt according to Example 15. [Diagram 5] FIG. 5 is a spectrum showing the particle size distribution of particles contained in the metal double salt dispersion liquid of Example 15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The metal double salt dispersion and metal oxide nanoparticle dispersion of the present invention will be described below. However, the present invention is not limited to the following configurations, and can be modified and applied as appropriate within the scope of the present invention. Note that the present invention also includes a combination of two or more of the individual desirable configurations described below.

[0020] [Metal double salt dispersion] The metal double salt dispersion of the present invention is a metal double salt dispersion containing an organic solvent and a metal double salt, and the metal double salt is M(R 1 COO) m-x-y (OH) x A y (H 2 O) z [where M is a metal element, R 1 is a hydrogen atom or an alkyl group, A is an anion, m is the valence of the metal element M, 0 <x+y<m、x> 0, y≧0, z≧0.], and when the metal double salt dispersion is centrifuged at a relative centrifugal force of 10,000 G for 5 minutes, the proportion of metal elements that do not form precipitates among all metal elements contained in the entire metal double salt dispersion is 10.0 mol % or more.

[0021] The metal double salt dispersion of the present invention is 1 COO) m-x-y (OH) x A y (H 2 O) z [where M is a metal element, R 1 is a hydrogen atom or an alkyl group, A is an anion, m is the valence of the metal element M, 0 <x+y<m、x> 0, y≧0, z≧0. The above metal double salts are carboxylates (R 1 COO - ), it has excellent affinity for organic solvents and is highly dispersible in organic solvents. In addition, the above metal double salts have hydroxide ions (OH - ), it can be easily converted to the metal oxide by heating at less than 100°C.

[0022] In the metal double salt dispersion of the present invention, when centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, the proportion of metal elements that do not form precipitates among all metal elements contained in the entire metal double salt dispersion is 10.0 mol % or more. In other words, even when the metal double salt dispersion of the present invention is subjected to a specified centrifugation operation, 10.0 mol % or more of all metal elements are dispersed in the solution, and it can be said that the dispersibility of the metal double salt is high.

[0023] In the metal double salt dispersion of the present invention, when centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, the proportion of metal elements that do not form precipitates among all metal elements contained in the entire metal double salt dispersion is preferably 12.6 mol % or more, and more preferably 30.0 mol % or more.

[0024] In the metal double salt dispersion of the present invention, the metal element M constituting the metal double salt preferably contains at least one metal selected from the group consisting of Cu, Mn, Co, Ce, Fe and In. In addition, when the metal element M contains two or more metal elements with different valences, the valence m of the metal element is the sum of the abundance ratio [mol%] of each metal element in the total metal elements multiplied by the valence of each metal element.

[0025] Functional group R constituting the metal double salt 1 It is preferable that the alkyl group contains at least one functional group selected from the group consisting of a hydrogen atom, a methyl group, an ethyl group, a 1-propyl group, and a 2-propyl group. Of these, a methyl group is preferred. The metal double salt dispersion of the present invention is also 1 It may be a mixture of two or more double salts having different structures.

[0026] The anion A that constitutes the metal double salt is the chloride ion (Cl - ), nitrate ion (NO 3 - ), carbonate ion (CO 3 2- ), sulfate ion (SO 4 2- ) etc. If the proportion of anion A is large, the proportion of carboxylate is relatively decreased, and the dispersibility of the double salt is decreased. Therefore, it is preferable that y is 0 or more and 1 or less.

[0027] In the composition formula of a metal double salt, z represents the number of bonds of water of hydration. If the number of bonds of water of hydration is large, the dispersibility of the double salt deteriorates. Therefore, z is preferably 0 or more and 4 or less.

[0028] The metal double salt dispersion of the present invention may contain, in addition to the organic solvent and the metal double salt, a salt of a carboxylic acid and a strong base, or a metal carboxylate. The salt of a carboxylic acid and a strong base is a by-product formed during the production of the double metal salt dispersion of the present invention. The metal carboxylate is an unreacted raw material used in the process of producing the metal double salt dispersion of the present invention.

[0029] Examples of the salt of a carboxylic acid and a strong base include tetramethylammonium acetate, diazabicycloundecene acetate, diazabicyclononene acetate, tetramethylguanidine acetate, and tetraethylammonium acetate. Of these, diazabicycloundecene acetate is preferred.

[0030] Examples of strong bases include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; quaternary ammonium hydroxides such as tetramethylammonium hydroxide (TMAH) and tetraethylammonium hydroxide (TEAH); organic bases having an amidine skeleton such as 1,8-diazabicyclo[5.4.0]undec-7-ene (also referred to as diazabicycloundecene or DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (also referred to as diazabicyclononene or DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene; and organic bases having a guanidine skeleton such as 1,1,3,3-tetramethylguanidine (also referred to as tetramethylguanidine or TMG). Among these, organic bases having an amidine skeleton or a guanidine skeleton are preferred, and diazabicycloundecene is more preferred.

[0031] As used herein, a strong base refers to a base whose base dissociation constant (pKb) in water is 2 or less, or whose conjugate acid has an acid dissociation constant (pKa) in water of 12 or more.

[0032] The carboxylic acid is R 2 COOH[where R 2 is a hydrogen atom or an alkyl group.] The functional group R constituting the carboxylic acid 2 is the functional group R constituting the metal double salt. 1 It is preferable that the ratio is the same as

[0033] Examples of the metal carboxylate include copper(II) acetate, manganese(II) acetate, cobalt(II) acetate, cerium(III) acetate, iron(II) acetate, and indium(III) acetate.

[0034] The metal element concentration in the metal double salt dispersion of the present invention is not particularly limited, but is preferably 0.0001 mol / L or more and 2.0 mol / L or less.

[0035] The type of organic solvent used in the metal double salt dispersion of the present invention is not particularly limited, but it is desirable for the organic solvent to have a Snyder polarity parameter of 3.5 or more. Examples of organic solvents having a Snyder polarity parameter of 3.5 or more include alcohols such as methanol and ethanol, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), 1-methyl-2-pyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone (DMI), pyridine, and the like.

[0036] The average particle size in a dry state of the metal double salt contained in the metal double salt dispersion of the present invention is preferably 1 nm or more and 5 nm or less. The above average particle size can be measured by a transmission electron microscope (TEM) and is the average value of particle sizes of 30 metal double salts randomly selected within a field of view.

[0037] The metal double salt dispersion of the present invention can be converted into a metal oxide nanoparticle dispersion by heating in the presence of water. In the metal oxide nanoparticle dispersion produced using the metal double salt dispersion of the present invention, carboxylate derived from the double salt is present on the surface of the metal oxide nanoparticles, and therefore the metal oxide nanoparticles are dispersed in a colloidal state in an organic solvent, and are thought to have excellent dispersibility.

[0038] When the metal double salt dispersion of the present invention is heated, it is preferable that 2 to 20 mol of water is present per 1 mol of the metal double salt. If the amount of water present exceeds 20 mol per mol of the metal double salt, the dispersibility of the metal oxide obtained by heating the metal double salt may decrease.

[0039] When producing a metal oxide nanoparticle dispersion liquid using the metal double salt dispersion liquid of the present invention, for example, a method can be used in which water is added to the metal double salt dispersion liquid and the mixture is heated at a temperature of 50°C or higher and lower than 100°C for 15 minutes or longer and 12 hours or shorter.

[0040] The metal double salt dispersion of the present invention can be used for purposes other than the above-mentioned use of producing the metal oxide nanoparticle dispersion. For example, a film containing a metal double salt can be formed using the metal double salt dispersion of the present invention, and then heated to form a thin film of a metal oxide. In addition, by mixing the metal double salt dispersion of the present invention with a base material, a material in which the base material and the metal double salt are combined can be obtained.

[0041] [Method of manufacturing metal double salt dispersion] The method for producing a metal double salt dispersion of the present invention includes a step of adding a strong base to a metal salt dispersion containing a metal carboxylate and an organic solvent, and is characterized in that, when the valence of a metal element constituting the metal carboxylate is m, the substance amount of the strong base relative to the substance amount of the metal carboxylate is 0.4 m or more and 0.9 m or less.

[0042] In the method for producing a metal double salt dispersion of the present invention, a strong base is added to a metal salt dispersion containing a metal carboxylate and an organic solvent so that the substance amount of the strong base relative to the substance amount of the metal carboxylate is 0.4 m or more and 0.9 m or less, where m is the valence of the metal element constituting the metal carboxylate. Therefore, the metal carboxylate dispersed in the organic solvent reacts with the strong base to form a metal double salt. The metal double salt obtained by reacting a metal carboxylate with a strong base is called a carboxylate (R 1 COO - ), it has excellent affinity for organic solvents and is highly dispersible in organic solvents. In addition, the above double salts have hydroxide ions (OH -) and can be easily converted to metal oxide by heating at less than 100°C. Therefore, by the method for producing a metal double salt dispersion of the present invention, a metal double salt dispersion having high dispersibility and reactivity can be produced. If the ratio of the strong base is less than 0.4 m, the metal double salt formed is difficult to convert to an oxide, whereas if the ratio of the strong base is more than 0.9 m, the dispersibility of the metal double salt formed is insufficient.

[0043] Examples of metal carboxylates used in the method for producing a metal double salt dispersion of the present invention include copper acetate (II), manganese acetate (II), cobalt acetate (II), cerium acetate (III), iron acetate (II), and indium acetate (III). These acetates may be hydrates. They may also contain multiple types of metal elements. In addition, when a metal carboxylate contains two or more metal elements with different valences, the sum of the abundance ratio [mol%] of each metal element in the total metal elements multiplied by the valence of each metal element is defined as the valence m of the metal elements constituting the metal carboxylate.

[0044] As the organic solvent and strong base used in the method for producing a metal double salt dispersion of the present invention, the same organic solvent and strong base as those constituting the metal double salt dispersion of the present invention can be used.

[0045] The metal salt dispersion can be obtained by mixing a metal carboxylate with an organic solvent.

[0046] The metal salt dispersion may be prepared using a method that does not use a metal carboxylate. When preparing a metal salt dispersion liquid without using a metal carboxylate, for example, a metal salt other than a metal carboxylate (e.g., a chloride, a nitrate, a sulfate, a carbonate, etc.), a carboxylic acid compound, and an organic solvent may be mixed.

[0047] In the step of adding the strong base to the metal salt dispersion, it is preferable to dropwise add the strong base while mixing the metal salt dispersion. The strong base may be added to the metal salt dispersion in a state dissolved or dispersed in an organic solvent. The strong base to be added may be one type or two or more types.

[0048] [Metal oxide nanoparticle dispersion] The metal oxide nanoparticle dispersion liquid of the present invention is characterized by containing metal oxide nanoparticles and an organic base having an amidine skeleton or a guanidine skeleton.

[0049] The metal oxide nanoparticle dispersion of the present invention contains an organic base having an amidine skeleton or a guanidine skeleton, which can enhance the stability over time of the dispersibility of the metal oxide nanoparticles in the metal oxide nanoparticle dispersion.

[0050] Examples of organic bases having an amidine skeleton include 1,8-diazabicyclo[5.4.0]undec-7-ene (also called diazabicycloundecene or DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (also called diazabicyclononene or DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, etc. Among these, diazabicycloundecene and diazabicyclononene are preferred. An example of an organic base having a guanidine skeleton is 1,1,3,3-tetramethylguanidine (also called tetramethylguanidine or TMG). Therefore, the organic base preferably contains at least one compound selected from the group consisting of diazabicycloundecene, diazabicyclononene, and tetramethylguanidine. When the organic base contains at least one compound selected from the group consisting of diazabicycloundecene, diazabicyclononene, and tetramethylguanidine, these compounds have large steric hindrance, and therefore it is presumed that metal oxide nanoparticles having these compounds attached thereto are prevented from approaching each other, making them less likely to aggregate, thereby increasing the stability of the dispersibility of the metal oxide nanoparticles over time.

[0051] The molar ratio of the content of the organic base to the content of the metal component constituting the metal oxide nanoparticles is preferably 0.03 or less. When the molar ratio of the content of the organic base exceeds 0.03, the proportion of impurities contained in the metal oxide nanoparticle dispersion is low, and inconveniences caused by impurities when using the metal oxide nanoparticle dispersion can be suppressed. The content of the organic base having an amidine skeleton or a guanidine skeleton contained in the metal oxide nanoparticle dispersion liquid can be measured by gas chromatography. Furthermore, the molar ratio of the content of the organic base to the content of the metal component constituting the metal oxide nanoparticles may be 0.001 or more, provided that it is equal to or greater than the detection limit of the organic base.

[0052] The organic base preferably contains at least one compound selected from the group consisting of diazabicycloundecene, diazabicyclononene, and tetramethylguanidine.

[0053] The metal component constituting the metal oxide nanoparticles preferably contains at least one metal selected from the group consisting of Cu, Mn, Co, Ce, Fe, and In. Two or more metals may be contained in the metal oxide nanoparticles. Furthermore, the type of metal component constituting the metal oxide nanoparticles and the type of metal oxide are not related to the dispersibility of the metal oxide nanoparticles in the metal oxide nanoparticle dispersion liquid.

[0054] The average particle size of the metal oxide nanoparticles constituting the metal oxide nanoparticle dispersion is preferably 1 nm or more and 20 nm or less, and more preferably 1 nm or more and 10 nm or less. When the average particle size of the metal oxide nanoparticles is within the above range, the dispersion stability over time is excellent. The average particle size of the metal oxide nanoparticles is the particle size at 50% of the cumulative number of the metal oxide nanoparticles (D50), measured by dynamic light scattering.

[0055] [Method of manufacturing metal oxide nanoparticle dispersion] The method for producing a metal oxide nanoparticle dispersion of the present invention includes a preparation step of adding a strong base to a metal salt dispersion containing a metal carboxylate and an organic solvent to prepare a metal double salt dispersion, and a heating step of heating the metal double salt dispersion in the presence of water to obtain the metal oxide nanoparticle dispersion, wherein in the preparation step, when the valence of a metal element constituting the metal carboxylate is m, the substance amount of the strong base relative to the substance amount of the metal carboxylate is 0.4 m or more and 0.9 m or less, and the strong base includes an organic base having an amidine skeleton or a guanidine skeleton.

[0056] By using the method for producing a metal oxide nanoparticle dispersion liquid of the present invention, it is possible to produce a metal oxide nanoparticle dispersion liquid in which the dispersibility of metal oxide nanoparticles has excellent stability over time. The metal oxide nanoparticle dispersion liquid produced by the method for producing a metal oxide nanoparticle dispersion liquid of the present invention is also the metal oxide nanoparticle dispersion liquid of the present invention.

[0057] The method for producing a metal oxide nanoparticle dispersion of the present invention corresponds to the method for producing a metal double salt dispersion of the present invention, in which an organic base having an amidine skeleton or a guanidine skeleton is used as a strong base and the obtained metal double salt dispersion is heated in the presence of water. Therefore, the explanation of the process for preparing the metal double salt dispersion will be omitted.

[0058] The organic base preferably contains at least one compound selected from the group consisting of diazabicycloundecene, diazabicyclononene, and tetramethylguanidine. Diazabicycloundecene, diazabicyclononene, and tetramethylguanidine can increase the stability of the dispersibility of metal oxide nanoparticles over time in a metal oxide nanoparticle dispersion liquid. In addition, diazabicycloundecene, diazabicyclononene, and tetramethylguanidine are easily identified as being contained in a metal oxide nanoparticle dispersion liquid.

[0059] The metal component constituting the metal oxide nanoparticles preferably contains at least one metal selected from the group consisting of Cu, Mn, Co, Ce, Fe and In.

[0060] The water may be added during the preparation of the metal double salt dispersion, or may be added separately after the preparation of the metal double salt dispersion. Examples of the water added during the preparation of the metal double salt dispersion include water of hydration contained in a metal carboxylate.

[0061] The amount of water present when the metal double salt dispersion is heated is preferably 2 to 20 times the amount of the metal components in terms of molar ratio.

[0062] The temperature and time for heating the metal double salt dispersion in the presence of water can be appropriately adjusted depending on the type and particle size of the metal oxide nanoparticles to be obtained. The heating temperature is, for example, 50°C or higher and lower than 100°C. The heating time is, for example, 15 minutes or more and 12 hours or less.

[0063] The metal oxide nanoparticle dispersion obtained by the above procedure may be purified as necessary. By purifying the metal oxide nanoparticle dispersion liquid, the content of the organic base contained in the metal oxide nanoparticle dispersion liquid can be reduced.

[0064] The procedure for purifying the metal oxide nanoparticle dispersion liquid includes, for example, adding an organic solvent such as methyl acetate to the metal oxide nanoparticle dispersion liquid, then centrifuging the metal oxide nanoparticles to precipitate them, removing the supernatant solution, and dispersing the metal oxide nanoparticles in the dispersion medium again. The above purification may be performed multiple times. By increasing the number of purification steps, the molar ratio of the content of the organic base to the content of the metal component constituting the metal oxide nanoparticles can be reduced.

[0065] The purification of the metal oxide nanoparticle dispersion liquid by the above procedure is preferably repeated until the molar ratio of the content of the organic base to the content of the metal component constituting the metal oxide nanoparticles becomes 0.03 or less. EXAMPLES

[0066] Examples are given below that more specifically disclose the metal double salt dispersion of the present invention, the method for producing the metal double salt dispersion of the present invention, the metal oxide nanoparticle dispersion of the present invention, and the method for producing the metal oxide nanoparticle dispersion of the present invention. Note that the present invention is not limited to these examples.

[0067] <Example 1> (Preparation of metal double salt dispersion) 9.23 mL of ethanol (ultra-dehydrated grade, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added to 0.2 g of copper (II) acetate monohydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and mixed at room temperature. 0.422 mL of a 25% methanol solution of tetramethylammonium hydroxide (TMAH) (manufactured by Sigma-Aldrich Co., Ltd.) was added dropwise to this solution while mixing at room temperature, thereby obtaining a metal double salt dispersion liquid according to Example 1. The substance amount of the strong base relative to the substance amount of the metal carboxylate was 1.00, and was 0.4 m or more and 0.9 m or less (m=2). The metal double salt dispersion liquid of Example 1 contained a copper double salt [Cu(CH 3 COO) 2-x (OH) x ], unreacted metal carboxylate copper(II) acetate, and tetramethylammonium acetate, a salt of a carboxylic acid and a strong base. In addition, the metal double salt powder separated from the obtained metal double salt dispersion was measured by Fourier transform infrared spectroscopy (FT-IR). The obtained spectrum showed that the carboxylate (R 1 COO - ) originates from 1400 cm -1 Near and 1600cm -1 Absorption near the hydroxide ion (OH - ) from 3200 to 3500 cm -1 Absorption was confirmed in the vicinity.

[0068] (Measurement of the amount of metal dispersed in a metal double salt dispersion) The metal double salt dispersion according to Example 1 was centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, and the supernatant was separated. The same volume of methyl acetate and 4 times the volume of heptane were added to the separated liquid and stirred, and then the liquid was centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, after which the supernatant was discarded and the residue was recovered. The recovered residue was thermally decomposed at 400° C. to obtain copper oxide (CuO), and the proportion of metal elements that did not form precipitates in the metal double salt dispersion (i.e., double salts in a dispersed state) was calculated from the weight of the copper oxide (CuO). The results are shown in Table 1.

[0069] (Preparation of metal oxide nanoparticle dispersion) A metal oxide nanoparticle dispersion was obtained by adding 0.131 mL of pure water to 5 mL of the metal double salt dispersion according to Example 1, and heating and mixing for 30 minutes in an oil bath at 70° C. The obtained metal oxide nanoparticle dispersion was separated and dried, and the solid content was measured by powder X-ray diffraction (XRD), confirming the presence of a peak derived from copper oxide (CuO).

[0070] (Measurement of the amount of metal dispersed in a metal oxide nanoparticle dispersion) Next, the same volume of methyl acetate and four times the volume of heptane were added to the obtained metal oxide nanoparticle dispersion and stirred, and then the mixture was centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, after which the supernatant was discarded and the residue was recovered. The recovered residue was thermally decomposed at 400°C to obtain copper oxide (CuO), and the proportion of metal elements that did not form precipitates in the metal oxide nanoparticle dispersion (i.e., oxides in a dispersed state) was calculated from the weight of the copper oxide (CuO). The results are shown in Table 1.

[0071] <Example 2> A metal double salt dispersion according to Example 2 was prepared in the same manner as in Example 1, except that the amount of ethanol added was changed from 9.23 mL to 8.92 mL, and the amount of 25% methanol solution of TMAH added was changed from 0.422 mL to 0.739 mL, and the proportion of dispersed double salts was measured. A metal oxide nanoparticle dispersion was also prepared in the same manner as in Example 1, and the proportion of dispersed oxides was measured. The results are shown in Table 1. The ratio of the substance amount of the strong base to the substance amount of the metal carboxylate was 1.75.

[0072] <Comparative Example 1> A metal double salt dispersion liquid according to Comparative Example 1 was prepared in the same manner as in Example 1, except that the amount of ethanol added was changed from 9.23 mL to 8.90 mL, and the amount of 25% methanol solution of TMAH added was changed from 0.422 mL to 0.802 mL. The proportion of the double salt in the dispersed state was measured. A metal oxide nanoparticle dispersion liquid was also prepared in the same manner as in Example 1, and the proportion of the oxide in the dispersed state was measured. The results are shown in Table 1.

[0073] <Example 3> (Preparation of metal double salt dispersion) 0.2 g of cobalt (II) acetate tetrahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was mixed with 7.27 mL of DMSO (ultra-dehydrated grade, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) at room temperature. 0.406 mL of a 25% methanol solution of TMAH (manufactured by Sigma-Aldrich Co., Ltd.) was added dropwise to this solution while mixing at room temperature, thereby obtaining a metal double salt dispersion according to Example 3. The obtained metal double salt dispersion was centrifuged at a relative centrifugal force of 10,000 G for 5 minutes, and the supernatant was separated. Four volumes of methyl acetate and four volumes of toluene were added to the separated liquid, and the mixture was stirred. The mixture was then centrifuged at a relative centrifugal force of 10,000 G for 5 minutes, the supernatant was discarded, and the residue was recovered. The recovered residue was thermally decomposed at 400 °C to obtain cobalt oxide (Co 3 O 4 The proportion of the double salt in a dispersed state in the metal double salt dispersion was measured from the weight of the double salt. The results are shown in Table 1.

[0074] (Preparation of metal oxide nanoparticle dispersion) 0.148 mL of pure water was added to 5 mL of the metal double salt dispersion of Example 3, and the mixture was heated in an oil bath at 95° C. for 2.5 hours to obtain a metal oxide nanoparticle dispersion of Example 3. The obtained metal oxide nanoparticle dispersion was centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, and the supernatant was separated. Methyl acetate in a volume four times that of the separated dispersion was added and stirred, and then the mixture was centrifuged for another 5 minutes at a relative centrifugal force of 10,000 G. The supernatant was discarded, and the residue was recovered. The recovered residue was thermally decomposed at 400° C. to obtain cobalt oxide (Co 3 O 4 The ratio of oxide dispersed in the metal oxide nanoparticle dispersion was calculated from the weight of the metal oxide nanoparticles. The results are shown in Table 1.

[0075] <Example 4> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 4 was prepared in the same manner as in Example 3, except that 0.2 g of manganese (II) acetate tetrahydrate [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.] was used instead of cobalt (II) acetate tetrahydrate, the amount of DMSO added was changed from 7.27 mL to 7.60 mL, and the amount of 25% methanol solution of TMAH added was changed from 0.406 mL to 0.344 mL, and the proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 3. The results are shown in Table 1.

[0076] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 3, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was changed to 0.055 mL, heating in the oil bath was changed to 70°C for 1 hour, and the amount of methyl acetate added to the separated metal oxide nanoparticle dispersion was changed to 7 times the volume of the separated liquid. The results are shown in Table 1.

[0077] <Example 5> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 5 was prepared in the same manner as in Example 3, except that 0.2 g of cerium (III) acetate monohydrate [manufactured by Nacalai Tesque, Inc.] was used instead of cobalt (II) acetate tetrahydrate, the amount of DMSO added was changed from 7.27 mL to 5.37 mL, and the amount of 25% methanol solution of TMAH added was changed from 0.406 mL to 0.377 mL. The proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 3. The results are shown in Table 1.

[0078] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 3, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was changed to 0.082 mL, heating in the oil bath was changed to 95°C for 1 hour, and the amount of methyl acetate added to the separated metal oxide nanoparticle dispersion was changed to 9 times the volume of the separated liquid, and the amount of methyl acetate added to the separated metal oxide nanoparticle dispersion was changed to 9 times the volume of the separated liquid. The results are shown in Table 1.

[0079] <Example 6> (Preparation of metal double salt dispersion) A metal double salt dispersion liquid of Example 6 was prepared in the same manner as in Example 3, except that 0.2 g of cobalt (II) acetate tetrahydrate and 0.0971 g of manganese (II) acetate tetrahydrate [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.] were used, the amount of DMSO added was changed from 7.27 mL to 5.48 mL, 5.48 mL of pyridine was added in addition to DMSO as an organic solvent, and the amount of 25% TMAH in methanol solution added was changed from 0.406 mL to 0.6065 mL. The proportion of double salts dispersed in the metal double salt dispersion was determined in the same manner as in Example 3, except that the solvent added to the separated metal double salt dispersion was methyl acetate in an amount four times the volume of the separated liquid, and toluene was not added. The results are shown in Table 1.

[0080] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 3, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was changed to 0.101 mL and heating in an oil bath was changed to 95° C. for 2 hours. The results are shown in Table 1.

[0081] <Example 7> (Preparation of metal double salt dispersion) The amount of cobalt (II) acetate tetrahydrate was changed from 0.2 g to 1.0 g, the amount of manganese (II) acetate tetrahydrate was changed from 0.0971 g to 0.485 g, the amount of DMSO and pyridine added was changed from 5.48 mL to 2.32 mL, and the amount of 25% methanol solution of TMAH added was changed from 0.6065 mL to 3.03 mL, but the same procedure as in Example 6 was used to prepare a metal double salt dispersion according to Example 7, and the proportion of double salts dispersed in the metal double salt dispersion was determined. The results are shown in Table 1.

[0082] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 6, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was set to 0 mL (i.e., no pure water was added) and heating in an oil bath was changed to 95°C for 7 hours. The results are shown in Table 1.

[0083] <Example 8> (Preparation of metal double salt dispersion) The metal double salt dispersion of Example 8 was prepared in the same manner as in Example 7, except that the amounts of DMSO and pyridine added were changed from 2.32 mL to 3.30 mL, and 1.07 mL of diazabicycloundecene (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 3.03 mL of a 25% methanol solution of TMAH. The proportion of double salts dispersed in the metal double salt dispersion was determined in the same manner as in Example 7, except that the solvent added to the separated metal double salt dispersion was changed to methyl acetate in an amount four times the volume of the separated solution and toluene in an amount six times the volume of the separated solution. The results are shown in Table 1.

[0084] (Preparation of metal oxide nanoparticle dispersion) The ratio of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 7, except that the solvent added during preparation of the metal oxide nanoparticle dispersion was changed to methyl acetate in an amount four times the volume of the separated solution and toluene in an amount six times the volume. The results are shown in Table 1.

[0085] <Example 9> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 9 was prepared in the same manner as in Example 3, except that the amount of cobalt (II) acetate tetrahydrate was changed from 0.2 g to 2.2 g, the amount of DMSO added was changed from 7.27 mL to 14.45 mL, and 1.85 mL of diazabicycloundecene was used instead of 3.03 mL of a 25% methanol solution of TMAH, and the proportion of double salts dispersed in the metal double salt dispersion was determined in the same manner as in Example 3. The results are shown in Table 1.

[0086] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 3, except that the amount of pure water added when preparing the metal oxide nanoparticle dispersion was changed to 0.023 mL, the heating in the oil bath was changed to 3 hours, air was introduced into the reaction solution while bubbling at a flow rate of 200 sccm during heating in the oil bath, and the solution added when preparing the separated metal oxide nanoparticle dispersion was changed to 4 times the volume of the separated solution of methyl acetate and 6 times the volume of toluene. The results are shown in Table 1.

[0087] <Example 10> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 10 was prepared in the same manner as in Example 9, except that the amount of DMSO added was changed from 14.45 mL to 14.82 mL, and 1.85 mL of diazabicycloundecene was replaced with 1.48 mL of diazabicyclononene (manufactured by Tokyo Chemical Industry Co., Ltd.), and the proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0088] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides in a dispersed state in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0089] <Example 11> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 11 was prepared in the same manner as in Example 9, except that the amount of DMSO added was changed from 14.45 mL to 14.74 mL, and 1.85 mL of diazabicycloundecene was replaced with 1.55 mL of tetramethylguanidine (manufactured by Tokyo Chemical Industry Co., Ltd.), and the proportion of the double salt in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0090] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides in a dispersed state in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0091] <Example 12> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 12 was prepared in the same manner as in Example 9, except that 1.5 g of copper (II) acetate monohydrate was used instead of cobalt (II) acetate tetrahydrate, the amount of DMSO added was changed from 14.45 mL to 12.61 mL, and the amount of diazabicycloundecene added was changed from 1.85 mL to 1.35 mL, and the proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0092] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 9, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was changed to 0.091 mL, the oil bath temperature was changed to 70°C, the heating time in the oil bath was changed to 1 hour, and the amount of air introduced into the reaction solution during heating in the oil bath was changed to 0 sccm. The results are shown in Table 1.

[0093] <Example 13> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 13 was prepared in the same manner as in Example 9, except that 1.5 g of manganese (II) acetate tetrahydrate was used instead of cobalt (II) acetate tetrahydrate, the amount of DMSO added was changed from 14.45 mL to 10.38 mL, and the amount of diazabicycloundecene added was changed from 1.85 mL to 0.932 mL, and the proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0094] (Preparation of metal oxide nanoparticle dispersion) The proportion of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 9, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was 0 mL, the oil bath temperature was changed to 70° C., and the heating time in the oil bath was changed to 2 hours. The results are shown in Table 1.

[0095] <Example 14> (Preparation of metal double salt dispersion) A metal double salt dispersion according to Example 14 was prepared in the same manner as in Example 9, except that 3.0 g of cerium (III) acetate monohydrate was used instead of cobalt (II) acetate tetrahydrate, 12.63 mL of NMP [ultra-dehydrated grade, Fujifilm Wako Pure Chemical Industries, Ltd.] was used instead of DMSO, and the amount of diazabicycloundecene added was changed from 1.85 mL to 3.34 mL. The proportion of double salts in a dispersed state in the metal double salt dispersion was determined in the same manner as in Example 9. The results are shown in Table 1.

[0096] (Preparation of metal oxide nanoparticle dispersion) The ratio of oxides dispersed in the metal oxide nanoparticle dispersion was determined in the same manner as in Example 9, except that the amount of pure water added during preparation of the metal oxide nanoparticle dispersion was 0.045 mL. The results are shown in Table 1.

[0097] [Table 1]

[0098] (Comparison of Dispersion State Between Example 1 and Comparative Example 1) The metal double salt dispersions and metal oxide nanoparticle dispersions prepared in Example 1 and Comparative Example 1 were each centrifuged for 5 minutes at a relative centrifugal force of 10,000 G, and the dispersion state was confirmed. The results are shown in Figures 1 and 2. Figure 1 is a photograph of the metal double salt dispersions of Example 1 and Comparative Example 1 after centrifugal operation, and Figure 2 is a photograph of the metal oxide nanoparticle dispersions of Example 1 and Comparative Example 1 after centrifugal operation. 1, precipitation was observed in the metal double salt dispersion liquid (right side) according to Comparative Example 1, whereas no precipitation was observed in the metal double salt dispersion liquid (left side) according to Example 1. Also, from Fig. 2, precipitation was observed in the metal oxide nanoparticle dispersion liquid (right side) according to Comparative Example 1, whereas no precipitation was observed in the metal oxide nanoparticle dispersion liquid (left side) according to Example 1. From these results, it was confirmed that the dispersibility of the metal double salt in the metal double salt dispersion liquid according to Example 1 and the dispersibility of the metal oxide nanoparticles in the metal oxide nanoparticle dispersion liquid were high. It is considered that in the metal oxide nanoparticle dispersion liquid produced using the metal double salt dispersion liquid of the present invention, the metal oxide nanoparticles are dispersed in a colloidal state and stabilized.

[0099] <Example 15> (Confirmation of metal double salts) 3.49 mL of ethanol was added to 0.4 g of copper (II) acetate monohydrate and mixed at room temperature. 0.299 mL of diazabicycloundecene was added dropwise to this solution while mixing at room temperature to prepare a metal double salt dispersion. Then, the solution was diluted with ethanol so that the metal concentration was 0.001 M. One drop of the diluted solution was dropped onto a slide film, which is a support film for TEM observation, and after drying, the portion on the slide film where the dispersion was dropped was observed by TEM. The results are shown in Figures 3 and 4. Figures 3 and 4 are TEM images of the metal double salt according to Example 15. From Figure 3, it was confirmed that the metal double salt dispersion contained metal double salt as particulate matter with particle diameters of approximately 1.5 nm to approximately 3.1 nm in the dry state. The average particle diameter of 30 metal double salts randomly selected from the field of view was 2.1 nm. Furthermore, from Figure 4, lattice fringes were observed in the particulate matter, confirming that the metal double salt was a crystalline substance.

[0100] (Confirmation of the average particle size of metal double salts using DLS and SAXS) For reference, the particle size of the particles contained in the metal double salt dispersion liquid prepared in the above confirmation of the metal double salt was measured by dynamic light scattering (DLS) and small angle X-ray scattering (SAXS). The results are shown in Figure 5. Figure 5 is a spectrum showing the particle size distribution of the particles contained in the metal double salt dispersion liquid of Example 15. The left side (solid line) is the DLS measurement result, and the right side (dashed line) is the SAXS measurement result. It was confirmed from Figure 5 that the DLS and SAXS results roughly correspond to the average particle size of the metal double salt measured by TEM.

[0101] (Example 16) (Preparation of metal double salt dispersion) Cobalt(II) acetate tetrahydrate and manganese(II) acetate tetrahydrate were weighed out so that the molar ratio of the metal components was 6:4, and added to DMSO [ultra-dehydrated grade, Fujifilm Wako Pure Chemical Industries, Ltd.] and mixed at room temperature to mix the metal salt with the organic solvent. To this mixture, 1.2 times the molar amount of DBU relative to the total amount of the metal components was added to obtain a metal double salt dispersion.

[0102] (Preparation of metal oxide nanoparticle dispersion) To the obtained metal double salt dispersion, pure water was added in an amount 0.5 times the total amount of metal components in terms of molar ratio, and the mixture was heated to 95°C while stirring and bubbling air in an atmospheric environment, and held for 2.5 hours to obtain a metal oxide nanoparticle dispersion.

[0103] (Refining metal oxide nanoparticle dispersions) Methyl acetate was added to the obtained metal oxide nanoparticle dispersion liquid, and the mixture was centrifuged at 10,000 G for 5 minutes to precipitate metal oxide nanoparticles. The supernatant solution was removed, and 2-propanol and diethylene glycol monoethyl ether were added to the precipitate to disperse it, and then heptane was added and the mixture was centrifuged at a centrifugal force of 10,000 G for 5 minutes to precipitate metal oxide nanoparticles. After the supernatant solution was removed, ethylene glycol monopropyl ether was added to the precipitate to disperse it, and a purified metal oxide nanoparticle dispersion liquid was obtained.

[0104] (Example 17) A metal oxide nanoparticle dispersion liquid according to Example 17 was produced in the same manner as in Example 16, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0105] (Example 18) A metal oxide nanoparticle dispersion liquid according to Example 18 was produced in the same manner as in Example 16, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0106] (Example 19) The metal oxide nanoparticle dispersion of Example 19 was produced using the same procedure as in Example 16, except that manganese (II) acetate tetrahydrate was not used and the amount of DBU added was changed to 1.4 times the molar ratio of cobalt.

[0107] (Example 20) A metal oxide nanoparticle dispersion liquid according to Example 20 was produced in the same manner as in Example 19, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0108] Example 21 A metal oxide nanoparticle dispersion liquid according to Example 21 was produced in the same manner as in Example 19, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0109] Example 22 The metal oxide nanoparticle dispersion of Example 22 was produced using the same procedure as Example 16, except that cobalt (II) acetate tetrahydrate was not used, the amount of DBU added was changed to 1.0 times the molar ratio of manganese, pure water was not added, and the heating temperature was changed to 70°C.

[0110] Example 23 A metal oxide nanoparticle dispersion liquid according to Example 23 was produced in the same manner as in Example 22, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0111] (Example 24) A metal oxide nanoparticle dispersion liquid according to Example 24 was produced in the same manner as in Example 22, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0112] (Example 25) The metal oxide nanoparticle dispersion of Example 25 was produced using the same procedure as in Example 16, except that copper(II) acetate monohydrate was used instead of manganese(II) acetate tetrahydrate and cobalt(II) acetate tetrahydrate, the amount of pure water added was changed to 2.0 times the molar ratio of copper, the heating temperature was changed to 75°C, and air bubbling was not performed during stirring.

[0113] (Example 26) A metal oxide nanoparticle dispersion liquid according to Example 26 was produced in the same manner as in Example 25, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0114] Example 27 A metal oxide nanoparticle dispersion liquid according to Example 27 was produced in the same manner as in Example 25, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0115] (Example 28) The metal oxide nanoparticle dispersion of Example 28 was produced using the same procedure as in Example 16, except that anhydrous iron(II) acetate was used instead of manganese(II) acetate tetrahydrate and cobalt(II) acetate tetrahydrate, and the amount of pure water added was changed to 4.0 times the molar ratio of iron.

[0116] (Example 29) A metal oxide nanoparticle dispersion liquid according to Example 29 was produced in the same manner as in Example 28, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0117] (Example 30) A metal oxide nanoparticle dispersion liquid according to Example 30 was produced in the same manner as in Example 28, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0118] (Example 31) The metal oxide nanoparticle dispersion of Example 31 was produced in the same manner as in Example 16, except that anhydrous indium(III) acetate was used instead of manganese(II) acetate tetrahydrate and cobalt(II) acetate tetrahydrate, the amount of DBU added was changed to 2.0 times the molar amount of indium, the amount of pure water added was changed to 4.0 times the molar amount of indium, and air bubbling was not performed during stirring.

[0119] Example 32 The metal oxide nanoparticle dispersion of Example 32 was produced using the same procedure as in Example 16, except that cerium (III) acetate monohydrate was used instead of manganese (II) acetate tetrahydrate and cobalt (II) acetate tetrahydrate, the amount of DBU added was changed to 2.5 times the molar amount of cerium, and the amount of pure water added was changed to 1.0 times the molar amount of indium.

[0120] (Example 33) A metal oxide nanoparticle dispersion liquid according to Example 33 was produced in the same manner as in Example 32, except that DBN in an amount equal to that of DBU was used instead of DBU.

[0121] (Example 34) A metal oxide nanoparticle dispersion liquid according to Example 34 was produced in the same manner as in Example 32, except that TMG in an amount equal to that of DBU was used instead of DBU.

[0122] Comparative Example 2 A metal oxide nanoparticle dispersion liquid according to Comparative Example 2 was produced in the same manner as in Example 16, except that a methanol solution of lithium hydroxide monohydrate (concentration: 2.0 M) was used in place of DBU in the same amount as DBU.

[0123] (Measurement of base amount) The molar ratio of the content of the organic base having an amidine skeleton or a guanidine skeleton contained in the purified metal oxide nanoparticle dispersion liquid to the substance amount of all metal components contained in the metal oxide nanoparticle dispersion liquid was measured by gas chromatography for the metal oxide nanoparticle dispersion liquids of Examples 16 to 34 and Comparative Example 2. The results are shown in Table 2.

[0124] (Measurement of the stability of dispersibility over time of metal oxide nanoparticle dispersion) The purified metal oxide nanoparticle dispersions according to Examples 16 to 34 and Comparative Example 2 were centrifuged at a relative centrifugal force of 10,000 G for 5 minutes, and the supernatant was collected and the concentration of the metal components contained in the supernatant was measured. The metal oxide nanoparticle dispersions were then sealed in glass bottles and left to stand for one week under conditions of a relative humidity of 50% and a temperature of 25°C, after which the concentration of the metal components was measured in the same manner, and the reduction in the rate of change of the metal oxide nanoparticles dispersed in the metal oxide nanoparticle dispersions before and after leaving them to stand was calculated. The results are shown in Table 2. When the rate of change in the dispersed metal oxide nanoparticles before and after being left standing for one week was reduced by less than 1.0%, the stability over time was evaluated as "good," and when it was reduced by 1.0% or more, the stability over time was evaluated as "poor."

[0125] (Measurement of the crystalline phase of metal oxide nanoparticles) The metal oxide nanoparticle dispersions according to Examples 16 to 34 and Comparative Example 2 were dried to obtain powders, and the crystal phases of the metal oxide nanoparticles were identified using a powder X-ray diffraction method, and the composition of the metal oxide nanoparticles was determined from the crystal phase. The results are shown in Table 2.

[0126] (Measuring the average particle size of metal oxide nanoparticles) Dynamic light scattering was used to measure the average particle size (D50) of the metal oxide nanoparticles dispersed in the metal oxide nanoparticle dispersions of Examples 16 to 34 and Comparative Example 2. The results are shown in Table 2.

[0127] [Table 2]

[0128] The results in Table 2 show that the metal oxide nanoparticle dispersions of Examples 16 to 34, in which an organic base having an amidine skeleton or a guanidine skeleton was used as the organic base, exhibited excellent stability of the dispersibility of the metal oxide nanoparticles over time.

Claims

1. Metal oxide nanoparticles, and R 2 COOH [where R 2 is a hydrogen atom or an alkyl group] and a salt of a strong base, A metal oxide nanoparticle dispersion liquid, characterized in that a metal component constituting the metal oxide nanoparticles contains at least one metal selected from the group consisting of Cu, Mn, Co, Ce, Fe and In.

2. The metal oxide nanoparticle dispersion liquid according to claim 1 , further comprising an organic base having an amidine skeleton or a guanidine skeleton.

3. 3. The metal oxide nanoparticle dispersion liquid according to claim 2, wherein a molar ratio of a content of the organic base to a content of a metal component constituting the metal oxide nanoparticles is 0.03 or less.

4. 4. The metal oxide nanoparticle dispersion liquid according to claim 2, wherein the organic base comprises at least one compound selected from the group consisting of diazabicycloundecene, diazabicyclononene, and tetramethylguanidine.

5. The metal oxide nanoparticle dispersion liquid according to any one of claims 1 to 4, which contains a solvent mainly composed of an organic solvent.

6. The metal oxide nanoparticle dispersion according to any one of claims 1 to 5, wherein a carboxylate is present on the surface of the metal oxide nanoparticles.

Citation Information

Patent Citations

  • Yttrium-or holmium-based compound redispersible in the form of gel

    JP1996319114A

  • Dispersant for inorganic powder

    JP2002179933A

  • Inspection port forming frame and wall structure having this inspection port forming frame

    JP2005139704A

  • Novel catalyst formulations and their preparation

    JP2005502446A

  • Method for producing metal oxide sol and metal oxide sol

    JP2006182604A